Can photobiomodulation therapy (PBMT) control blood glucose levels and alter muscle glycogen synthesis? - Castro, Kenia Mendes Rodrigues; de Paiva Carvalho, Rodrigo Leal [UNESP]; Junior, Geraldo Marco Rosa; Tavares, Beatriz Antoniassi; Simionato, Luis Henrique; Bortoluci, Carlos Henrique Fachin; Soto, Claudio Alberto Tellez; Ferraresi, Cleber (Elsevier, 2020)
Photobiomodulation therapy (PBMT) has many effects on the energy metabolism of musculoskeletal tissue, such as increased glycogen and adenosine triphosphate synthesis. In addition, these effects may be due to a systemic blood glucose control. Twenty-four Wistar rats were randomly and equally allocated into four groups: sham, PBMT 10 J/cm2, PBMT 30 J/cm2 and PBMT 60 J/cm2. The animals were fasting for 6 h for blood glucose evaluations during pre-irradiation period, 1 h, 3 h and 6 h after PBMT. Muscle glycogen synthesis was measured 24 h after PBMT. This PBMT used a cluster of 69 LEDs (light-emitting diodes) with 35 red (630 ± 10 nm) and 34 infrared (850 ± 20 nm); 114 mW/cm2 for 90s (10 J/cm2), 270 s (30 J/cm2), 540 s (60 J/cm2) applied on large muscle areas (back and hind legs) of the animals. The 10 J/cm2 group showed lower blood glucose levels and glucose variability over 6 h (5.92 mg/dL) compared to the sham (13.03 mg/dL), 30 J/cm2 (7.77 mg/dL) and 60 J/cm2 (9.07 mg/dL) groups. The PBMT groups had the greatest increase in muscle glycogen (10 J/cm2 > 60 J/cm2 > 30 J/cm2 > sham), characterizing a triphasic dose-response of PBMT. There was a strong negative correlation between blood glucose variability over 6 h and muscle glycogen concentration for 10 J/cm2 group (r = −0.94; p < .001) followed by 30 J/cm2 group (r = −0.84; p < .001) and 60 J/cm2 group(r = −0.73; p < .006). These results suggest that PBMT can play a very important role in the control of blood glucose levels, and its possible mechanism of action is the induction of greater muscle glycogen synthesis independently of physical exercise.
Keywords: Blood glucose; Diabetes mellitus; Glycogen; LED therapy; Low-level laser therapy